Top executive tournament incentives and corporate innovation output. (8th September 2021) - Cai, Xianjun; Pan, Huifeng; Gao, Chengcheng; Wang, Chunyang; Lu, Liping
Abstract: We examine the impact of tournament incentive on corporate innovation output in China. Using a sample of Chinese listed firms during 2007–2015, we find that tournament incentives have a positive effect on the quantity and quality of innovation output. This relationship is more pronounced in the context of a higher probability of promotion, e.g. prior to CEO turnover. Besides, this effect is stronger for private firms than for state‐owned enterprises (SOEs). Our results are robust to instrumental variable regression and other robustness checks. The paper casts light on the role of tournament incentives on corporate executives for policymakers to enhance corporate innovation.